Designing and Managing Industrial Product-Service Systems. - Helo, Petri (Springer Science and Business Media : Springer, 2016)
This book is dedicated to the issues and complexities of industrial services supply chain management. It analyzes how the transition from products to services can be managed, and how supply chains can be adjusted to reflect this new status quo. The book begins with chapters examining product-service systems structures and servitization--the services infusion process. Next, it presents industrial services as marketing and operations strategy. The focus shifts to service delivery, and this chapter discusses how the actual operations take place. This is followed by an examination of the role of technology and how connected assets are utilized by product vendors in value-creation. The book analyzes the transition from ownership to subscriptions in the pricing decisions chapter. Then the value chain effects chapter offers an overview of the mechanisms through which industrial companies are shortening the distance to end-users and aim for a better position in the value chain. Finally the conclusion addresses theoretical and empirical implications in the industrial services supply chain management.
Keywords: Business logistics.; elektronické knihy; electronic books